Corporate Governance Mechanisms and Shareholder Expropriation of the Malaysian Listed construction Companies - Zui, Boon Chiang (2016)
The construction industry plays an important role in the Malaysian economy development. However, there are reports that have disclosed the main predicament confronting this industry – a prevailing weak corporate internal control. As a result, the interests of shareholder are not protected by the management but expropriated. The main objective of this research therefore is to examine the relationship between the corporate governance (CG) elements and shareholder expropriation in Malaysian construction listed companies. As a longitudinal study of 37 public listed construction companies in the Main Board of the Bursa Malaysia over the period 2007 to 2011, this study discusses the influence of the CG elements: CEO duality, shareholder activism by institutional, independent director with tertiary education, corporate diversification, and family-ownership structure on monitoring the shareholder expropriation. The control variables such as firm size, firm age, and profit leverage are included in the model to reduce the likely effects that can invalidate the results. Firm performance as the proxy of shareholder expropriation is measured by using the Net Profit Margin and Dividend Payout Ratio. Using Ordinary Least Square and Fixed Effects Model analysis methodology, the findings suggested that there is linear relationship between family-ownership structure and shareholder expropriation. However, the Pearson correlation analysis has suggested that the correlation of family-ownership structure to shareholder expropriation is weak. As a conclusion, the findings in this study contradict the predictions of the theories and concepts examined here except for the family ownership structure. Therefore, it is recommended that the period of study could be extended and also to include other related industries such as the property sector. In addition, a longer period of study will probably show the likely influences of changes in the CG system of a company, with different results.